Safeguard Measures on Imports of Solar Cells and Modules - Al Murfie, Hadra; Syahrani, Lala; Absya Ripasada, Mohammad; Feisya Kamal, Nurul; Nabila, ⁠Rifa (As- Sakinah Law Firm & Society of Visual Informatics, 2023)
Within the context of the escape clause concept in international trade law, this articleanalyses the trade safeguard measures that the United States of America has enacted onimports of crystalline silicon photovoltaic (CSPV) cells and modules. An examination of thereasoning behind the United States’ decision to adopt these controls by Section 201 of theTrade Act of 1974 is presented in this article. The study highlights the detrimental effects ofincreased imports and trade on the domestic solar industry. The purpose of this study is todetermine whether or not these measures are by the conditions that are described in theescape clauses of the General Agreement on Tariffs and Trade (GATT) and the Agreementon Safeguards.